STEM Teachers’ Use of E-Learning Resources in Scripted Lessons: Endeavours Toward Teacher Professional Development - Christopher Mutseekwa; Cefas Nyasha Zimuto; Kevin Manunure; Jones Maeresera (Scientia Publica Media, 2025)
Globally, teacher professional development is increasingly gaining recognition as an intervention that ensures practitioners are equipped with the teaching competencies needed to keep abreast of a rapidly evolving educational environment. Developing professional competencies is critical to a science, technology, engineering, and mathematics (STEM) teacher’s growth. Empirical studies indicate that regular STEM teacher professional development (STEM-TPD) is necessary to develop these competencies. Drawing on the Technological, Pedagogical, and Content Knowledge (TPACK) framework, this mixed-methods study examines how beneficiaries of a Continuous Professional Development Certificate in Innovative Teaching Mathematics and Science (CPD ITMS) apply acquired skills to integrate e-learning resources into the teaching rehearsals of STEM subjects. Four purposively selected teachers take turns teaching scripted Mathematics, Biology, and Chemistry lessons. The teachers and one hundred and seventy (170) learners are participants in the study. Data is generated from Lesson Observations and Focus Group Discussions (FGDs) sessions. Findings reveal that the teachers’ abilities to integrate e-learning resources in teaching and learning were at different levels. The majority of them applied integration strategies that were teacher-centered rather than learner-centered. Other findings show that teachers’ inability to navigate within the Technological Pedagogical Knowledge (TPK) and Pedagogical Content Knowledge (PCK) aspects of the TPACK caused most of their challenges. Overall, lesson scripting provided for consistent teacher rehearsals and learners’ engagement that potentially heightened opportunities for teacher professional growth and sustained STEM-learning motivation for students. The study recommends sandwiched scripting that alternates with non-scripted, individually designed lessons to wean STEM teachers into sustainable capacity development.